(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The first stage in preparing the horticulture industry for creating adaptation plans under climate change scenarios is to quantify the effects of temperature fluctuations, surplus and restricted moisture conditions. Individual crop effects have been studied and assessed throughout the main agro-ecological areas and growing seasons. Scientific validation is required for production methods that may be modified to adapt for climate change. Although production regions for particular crops or the time of sowing and planting may be altered the markets windows as well as infrastructure, like the availability of local packaging as well as the distribution facilities, are important components to consider for many horticultural commodities. It’s expected to change key interactions among horticultural plants as well as pollinators, insects, disease, pests, weeds, pests as well as weeds. Because horticulture-based agricultural systems offer a great potential for sequestering carbon for climate change mitigation, there is a need for a fast and clear knowledge of the effect of climate change on horticultural crops in order to develop a solid action plan. Perennial tree work as carbon sinks by sequestering carbon from the atmosphere. The clean development method may be used to get the carbon credits. Based on location-specific climate smart horticulture concepts, an integrated strategy with all available choices will be most successful in maintaining production under climate change circumstances.